1989
DOI: 10.1523/jneurosci.09-07-02575.1989
|View full text |Cite
|
Sign up to set email alerts
|

Three conductance classes of nicotinic acetylcholine receptors are expressed in developing amphibian skeletal muscle

Abstract: Two previously described classes of nicotinic AChRs in vertebrate skeletal muscle have conductances of 40 and 60 pS. In addition, a third conductance class of AChR channels is present in developing Xenopus muscle. This class appears to represent an independent channel type, rather than a subconductance state of the larger conductance channels. The channel has a slope conductance of 25 pS and a reversal potential of about 0 mV membrane potential. Its kinetic properties resemble those of the 40 pS channels prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Recordings from BC3H-1 cells (27) have not revealed multiple conductance levels of AcChoRs such as we observed in oocytes; however, AcChoR channels with conductances lower than 40 pS have been reported in Xenopus muscle in vivo (7,8,28) and in denervated mouse muscle (29). One of these, a 25-pS channel, has been well characterized in developing Xenopus muscle (8).…”
mentioning
confidence: 47%
See 2 more Smart Citations
“…Recordings from BC3H-1 cells (27) have not revealed multiple conductance levels of AcChoRs such as we observed in oocytes; however, AcChoR channels with conductances lower than 40 pS have been reported in Xenopus muscle in vivo (7,8,28) and in denervated mouse muscle (29). One of these, a 25-pS channel, has been well characterized in developing Xenopus muscle (8).…”
mentioning
confidence: 47%
“…Although both kinds of receptors assemble less efficiently and the 8-less receptors have reduced agonist affinity (5), the weak responses to AcCho might also reflect a reduced conductance or a briefer open time. We were interested in examining the properties ofthese receptors because they might offer an explanation for the small conductance channels (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) pS) observed in developing amphibian muscle (7,8). We injected mRNAs encoding the mouse a, 3, y, and 8 subunits into Xenopus oocytes and found that multiple conductance classes of channels were expressed on the oocyte membrane, and one of these, the smallest, is due to deletion of the 8 subunit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Outside out patches were primarily taken from the middle of the muscle and it is possible that we recorded from membrane that contained junctional and extrajunctional receptors. But we do not have any evidence to indicate that synaptic receptors are different from extrasynaptic ones, and findings from rats and Xenopus have indicated that junctional and extra‐junctional channels are identical (Hamill and Sakmann, ; Kullberg et al, ; Brehm et al, ; Brehm and Kullberg, ; Owens and Kullberg, ).…”
Section: Discussionmentioning
confidence: 79%
“…Why are there two classes of acetylcholine receptors in body wall muscles? First, the multiple acetylcholine receptors could provide kinetically and pharmacologically diverse responses [26][27][28] . For example, in chicken sympathetic neurons, multiple acetylcholine receptor subtypes with distinct single-channel conductances and kinetics 29 form homogeneous clusters, which are spatially segregated in the same neuron 26 .…”
Section: Discussionmentioning
confidence: 99%